2019
DOI: 10.1021/acsomega.9b03109
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Preparation of 1-Aryl-Substituted 1,2,4-Triazolium Salts

Abstract: 1,4-Diaryl- and 1-aryl-4-alkyl-substituted 1,2,4-triazolium salts are convenient air-stable precursors to carbenes used both as organocatalysts or as ligands for transition metal complexes. Traditionally, they are prepared via a multistep synthetic pathway with the low-yielding formation of the triazolium ring occurring in the last step. We have developed an alternative two-step synthesis involving the conversion of a primary amine or aniline derivative to the corresponding 4-substituted triazole followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Triazole, 3a , was prepared according to the literature procedure shown in Scheme 2 [ 46 , 48 ]. While the p -methoxybenzyl-protected aniline, 2a , could be obtained in this case by protecting 2-mercaptoaniline, 1a , under argon atmosphere, the lack of commercial availability of substituted 2-mercaptoanilines required the development of a different synthesis route.…”
Section: Resultsmentioning
confidence: 99%
“…Triazole, 3a , was prepared according to the literature procedure shown in Scheme 2 [ 46 , 48 ]. While the p -methoxybenzyl-protected aniline, 2a , could be obtained in this case by protecting 2-mercaptoaniline, 1a , under argon atmosphere, the lack of commercial availability of substituted 2-mercaptoanilines required the development of a different synthesis route.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, diaryliodonium salts offer the possibility of selectively arylating the N-1 position of 4- www.eurjoc.org substituted triazoles containing other nucleophilic atoms. [57] To explore the limits of the electron-donating and electron-withdrawing effects on the oxidative cyclization reaction, we synthesized a range of N-arylated triazolium salts 2 a-g by reacting 1 with a variety of diaryliodonium salts prepared by known literature procedures. [58,59] We found that carrying out the copper-catalyzed quaternization of triazole 1 gave the best isolated yields when the reaction was carried out in the presence of 1.1 equivalents instead of 1.5 equivalents of the diaryliodonium salt and the reaction time was increased from 4 h to overnight (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, diaryliodonium salts offer the possibility of selectively arylating the N‐1 position of 4‐substituted triazoles containing other nucleophilic atoms [57] . To explore the limits of the electron‐donating and electron‐withdrawing effects on the oxidative cyclization reaction, we synthesized a range of N ‐arylated triazolium salts 2 a – g by reacting 1 with a variety of diaryliodonium salts prepared by known literature procedures [58,59] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations